PENGARUH PENGELUARAN MODAL, PENELITIAN DAN PENGEMBANGAN, TRANSAKSI PIHAK HUBUNGAN ISTIMEWA DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Arnida Wahyuni Lubis; Rina Bukit; Tapi Anda Sari Lubis (Program Magister Akuntansi Unsyiah, 2013)
The purpose of this study was to simultaneously and partially test the influence of capital expenditure, research and development, transaction of special relationship party and profitability on the company value. The population of this study was 131 manufacturing companies registered in the Indonesian Stock Exchange in 2012 and 51 of them were selected to be the samples for this study through purposive sampling technique. The result of this study showed that the influence of capital expenditure, research and development, transaction of special relationship party and profitability had a significant influence on the company value.Keywords: Capital Expenditure, Research and Development, Special Relationship Party Transaction, Profitability, Company Value